Improve Learning Results Using The Problem Based Learning Model - Ariyanto Ariyanto (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve learning outcomes in theme 4 using the Problem Based Learning Model. The research cond ucted was a Classroom Action Research (PTK) consisting of three cycles, with each cycle consisting of a pre-test meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting was conducted with a post test to determine the development of students. In the first cycle the students who completed after carrying out the post test were 66.66%. In the second cycle students who completed after carrying out the post test were 92%. In cycle III the students who completed after carrying out the post test were 100%. These results indicate that the Project Based Learning (PjBL) learning model can improve student learning outcomes, especially the theme 4 Class V at SDIT Nurul Islam Butuh.